The Pengaruh Psychological Well Being, Time Preassure, Dan Pengalaman Auditor Terhadap Kualitas Audit Dengan Role Stress Sebagai Variabel Moderasi - Farhan Dwinanda; Dwi Ayu Siti Hartinah H; Nur Abshari Abbas (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
This study aims to determine the influence of Psychological Well-Being, Time Pressure, and auditor experience on Audit Quality and how Role Stress can moderate the influence of Psychological Well-Being, Time Pressure, and auditor experience on Audit Quality. This type of research is quantitative research. The number of samples in this study was 35 auditors in the Inspectorate of South Sulawesi Province. This research instrument used a questionnaire, then the collected data will be analyzed using the IBM SPSS Ver. 26 application. The analysis method used is multiple linear regression and moderation analysis. The results show that there is an influence between Psychological Well-Being and Time Pressure of auditors on Audit Quality, but auditor experience does not affect audit quality. A more interesting finding is that with Role Stress as a Moderating Variable and strengthens the influence of Psychological Well-Being and Time Pressure on Audit Quality, this shows that, for individuals who have good mental health, role pressure is not an obstacle, but rather a driving force that motivates them to work more carefully and effectively, thereby improving audit quality overall. However, the Role Stress variable is unable to moderate and strengthen the influence between auditor experience and audit quality.